A genetic algorithm based distance-aware routing protocol for wireless sensor networks. (November 2016) - Bhatia, Tarunpreet; Kansal, Simmi; Goel, Shivani; Verma, A.K.
Highlights: A new cluster head selection algorithm in wireless sensor networks, coined as GADA-LEACH is proposed to reduce energy dissipation and improve the network lifetime. It makes use of Genetic Algorithm (GA) for optimized CH selection and concept of relay node for Distance Aware (DA) routing. Fitness function incorporates residual energy of nodes, distance between CH and nodes, and distance of BS from all CH's for better CH selection. Abstract: A Wireless Sensor Network (WSN) is an aggregation of sensor nodes which are remotely deployed in large numbers, operate autonomously in an unattended environment and have limited energy resource. In most of the hierarchical routing protocols, the cluster head (CH) selection is on the basis of random probability equation. There is a scope to reduce the energy dissipation by improving CH selection procedure. The proposed scheme, coined as GADA-LEACH, makes use of evolutionary genetic algorithm for improving CH selection in legacy LEACH routing protocol in sensor networks. The concept of relay node is introduced which acts as an intermediary between CH and base station (BS) to ease the communication between the CH and BS. The simulation results obtained supports that our proposed algorithm is efficient in terms of network lifetime. Graphical abstract: